Enhancement of the Sedimentation Rate of Copper Tailings by Application of Acoustic Fields - Gaete-Garreton, L; Vargas-Hernandez, y; Meneses-Díaz, J (Elsevier Ltd, 2020)
The rate of sedimentation in tailings thickeners in the mining industry is negatively affected when ultra-fine particles like clays or over-grinded particles appear in the concentration process. Such particles, sized less than 50 µm, reduce speed severely thus generating sedimentation suspensions. This harmful effect must be compensated with a reduction in the feeding rate, putting the entire upstream operation at risk. In the present study, results of the application of transversal and longitudinal ultrasound waves are shown in the sedimentation of tailings from copper mining to establish if the process can be accelerated. For this purpose, a rotating sedimentation system was designed and manufactured. It included sedimentation tubes equipped with electroacoustic transducers to stimulate the system in various ways during the sedimentation process. Different sedimentation experiments were developed to evaluate the effect of the excitation frequency and the position of the transducers. In each experiment, the copper tailings sample was mixed in the tube with anionic flocculant and subjected to ultrasonic fields with different frequencies to determine the tailings samples’ settling characteristics. It was found that the applied ultrasonic treatment positively affected the tailings processing and improved the speed of sedimentation. © 2019 Elsevier Ltd